Steganografi pada Citra Digital dengan Metode Cat Map dan Outguess - Bahtera Alam Wijaksono (Universitas Indraprasta PGRI Jakarta, 2017)
Steganography more commonly known as hiding some message in a picture, on this methods that have previously known as cryptographic. Development methods steganography more better then cryptographic, where method steganographic not limited to only one method. On case using file images or call stego images more secure and suspected by others who do not have assess right to the files. Method be compare of Least Significant Bit (LSB) and the End Of File (EOF)of course, each method has advantages and disadvantages Through this researchanalyze which method is more effective and efficient to hide a short message in the form of text format. In addition, the results of the literature study authors wanted to develop the application of steganography. See and learn both methods is expected that development will do better and be able to cover the shortfall the previous.